Use of threshold electrolyte concentration analysis to determine salinity and sodicity limit of irrigation water - Menezes,Heitor R. de (2014)
ABSTRACT This research studied threshold electrolyte concentration (TEC) of irrigation water and its effect on the infiltration rate of two contrasting soils from Pernambuco state, Brazil. The experiment was conducted in the Soil Chemistry and Salinity Laboratory of Federal Rural University of Pernambuco. Each soil was packed in five Buchner funnels, where one funnel from each soil was submitted to treatment with solution of electrical conductivity (EC) of 0.5, 1.0, 2.0, 4.0 or 8.0 dS m-1. For each funnel containing soil, an increasing ratio of NaCl to CaCl2 was applied in a treatment solution to achieve 10 increasing values of sodium adsorption ratio (SAR) from 0 to 100. These solutions were applied through a Mariotte bottle, with a constant hydraulic head of ~2 cm (pressure potential). After a liter of solution had drained, in the flux was collected for a known time interval, until steady state was reached. Darcy’s equation was used to calculate saturated hydraulic conductivity (Ksat) and a mathematical model used to calculate the TEC as a 20% reduction in Ksat. By increasing SAR similar behavior was noted between the two soils, whereby Ksat decreased, although the relativedecrease in Ksat was greater for SAR of 100 in the soil with higher clay content.